Variasi Konsentrasi Larutan Fiksasi Etanol Terhadap Kualitas Hasil Pewarnaan Hematoksilin Eosin pada Jaringan Histologi Ginjal Mencit - Azizah, Muti'ah Nur; Nailufar, Yuyun; Rahmawati, Yeni (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Fixation is a crucial step in the preparation of histology slides, working in maintaining the tissue structure in its original condition. This study aims to determine the effect of variations in the concentration of ethanol fixation solution on the quality of hematoxylin eosin (HE) staining results in mouse (Mus musculus) kidney histology tissue. This laboratory experimental study utilized three variations in ethanol concentrations (60%, 70%, 80%) and 10% Neutral Buffered Formalin (NBF) as a control, with a total of 24 mouse kidney slides. The quality of the preparations was assessed based on the parameters of nuclear color, cytoplasmic color, morphological integrity, color uniformity, and nuclear swelling. The results showed that fixation with 60% ethanol produced a preparation of poor quality, while 70% and 80% ethanol produced good quality, equivalent to the 10% NBE control. The Kruskal-Wallis and Mann-Whitney statistical tests showed a significant difference between the 60% ethanol group and the other groups (p < 0.05), but there was no significant difference between 70%, 80%, and 10% NBF. The conclusion of this study indicates that 70% and 80% ethanol have the potential to be effective and safer alternative fixatives compared to formalin. Keywords: Ethanol, Fixation, Hematoxylin and Eosin, Mouse Kidney